The DNA sequence of the H-2kb gene: evidence for gene conversion as a mechanism for the generation of polymorphism in histocompatibilty antigens. - Weiss, E (1983)
We have determined the DNA sequence of the H-2Kb gene of the C57B1/10 mouse. Comparison of this sequence with that of the allelic H-2Kd shows surprisingly that the exons have accumulated more mutations than their introns. Moreover, many of these changes in the exons are clustered in short regions or hot spots. Additional comparison of these sequences with the H-2Ld and H-2Db sequences shows that, in several cases, the altered sequence generated at the hot spot is identical to the corresponding region of a non-allelic H-2 gene. The clustered changes are responsible for 60% of the amino acid differences between the H-2Kb and H-2Kd genes and suggest that micro-gene conversion events occurring within the exons and involving only tens of nucleotides are an important mechanism for the generation of polymorphic differences between natural H-2 alleles.